2020
DOI: 10.3390/molecules25235488
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Soluble Epoxide Hydrolase Inhibitors in Multitarget and Combination Therapies for Inflammation and Cancer

Abstract: The enzyme soluble epoxide hydrolase (sEH) plays a central role in metabolism of bioactive lipid signaling molecules. The substrate-specific hydrolase activity of sEH converts epoxyeicosatrienoic acids (EETs) to less bioactive dihydroxyeicosatrienoic acids. EETs exhibit anti-inflammatory, analgesic, antihypertensive, cardio-protective and organ-protective properties. Accordingly, sEH inhibition is a promising therapeutic strategy for addressing a variety of diseases. In this review, we describe small molecule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 171 publications
(191 reference statements)
1
18
0
Order By: Relevance
“…Prior studies on other cancer types have demonstrated the anticancer effects of fenofibrate [ 49 ]. Small-molecule inhibition of sEH via Trans-AUCB similarly reduced PDAC cell viability, consistent with prior studies on other cancer types [ [50] , [51] , [52] , [53] ]. Notably, in our study, the combination of fenofibrate plus trans -AUCB yielded improved anticancer effects compared with either treatment alone.…”
Section: Discussionsupporting
confidence: 87%
“…Prior studies on other cancer types have demonstrated the anticancer effects of fenofibrate [ 49 ]. Small-molecule inhibition of sEH via Trans-AUCB similarly reduced PDAC cell viability, consistent with prior studies on other cancer types [ [50] , [51] , [52] , [53] ]. Notably, in our study, the combination of fenofibrate plus trans -AUCB yielded improved anticancer effects compared with either treatment alone.…”
Section: Discussionsupporting
confidence: 87%
“…MeOH (1 mL) and KOH (116 mg, 2.07 mmol) were added, and the mixture was stirred at 50 • C for 4 h. Amberlite ® 120 H+ was added until pH = 4 and the mixture was filtered, using MeOH as an eluting agent. Solvents were concentrated in vacuo to afford a white solid that was purified by column chromatography in silica gel (SiO 2 , DCM/MeOH mixtures) and gave 10d as a reddish solid (16 To a solution of 9-chloro-5,6,8,9,10,11-hexahydro-7H-5,9:7,11-dimethanobenzo [9] annulen-7-amine (88 mg, 0.36 mmol), 2e, in DMF (2 mL), 2-(1-(4-(t-butoxycarbonyl)phenyl) piperidin-4-yl)acetic acid (125 mg, 0.39 mmol), 9c, HATU (203 mg, 0.53 mmol), and DIPEA (124 µL, 92 mg, 0.71 mmol) were added. The mixture was stirred at room temperature overnight.…”
Section: Synthesis Of 2-(1-(2-bromo-4-(methoxycarbonyl)phenyl)piperidin-4-yl)acetic Acid 9dmentioning
confidence: 99%
“…Taking into account that several adamantane-based and benzene-based ureas are endowed with very potent activity as sEHI [14][15][16][17], that both AR9281 and EC5026 feature an acylpiperidine unit, and that the highly hydrophobic pocket of sEH seems able to accommodate very large hydrophobic groups [18], we have recently designed, synthesized and pharmacologically evaluated a novel series of ureas featuring the benzohomoadamantane scaffold as hydrophobic moiety, that merges in its polycyclic structure an adamantane-related core with an aromatic ring [19]. Several of these novel sEHI-based ureas were low nanomolar inhibitors of the human and murine sEH, but most of them, as 1, showed high melting points, limited solubility, and unacceptably low microsomal stabilities (Figure 2) [19].…”
Section: Introductionmentioning
confidence: 99%
“…Because EETs are rapidly metabolized by soluble epoxide hydrolase (sEH) to the less active dihydroxyeicosatrienoic acids (DiHETEs) ( 62 ), inhibition of sEH stabilizes EETs ( 62 , 65 ). Indeed, sEH is a key therapeutic target for pain, as well as neurodegenerative and inflammatory diseases, including cancer ( 33 , 35 , 65 – 74 ). Thus, sEH regulates inflammatory responses ( 62 ).…”
mentioning
confidence: 99%
“…Chronic pancreatitis is essential for the induction of pancreatic ductal adenocarcinoma by K-Ras oncogenes in adult mice, suggesting that inflammation is a critical driver of pancreatic cancer ( 76 , 77 ). Potent, selective inhibitors of sEH have been demonstrated to suppress human cancers (e.g., glioblastoma) and inflammation-induced carcinogenesis ( 67 , 71 ). Similarly, inhibition of sEH can suppress inflammatory bowel disease-induced carcinogenesis and inflammation-associated pancreatic cancer ( 74 , 78 ).…”
mentioning
confidence: 99%